Implementasi Kewajiban Notaris untuk Melekatkan Sidik Jari Para Penghadap pada Minuta Akta - Rizka Rahmawati (SASI, 2019)
The unclear setting regarding the notary's obligation to attach the fingerprints of the viewers influences the implementation of these provisions. There is a vagueness of norms against the provisions of Article 16 paragraph (1) letter c UUJN-P because they are not explained in detail. In addition, there is also a norm conflict in Article 16 paragraph (1) letter c UUJN-P with Article 38 paragraph (4) UUJN-P number 2 concerning attachment of fingerprints. The problem is whether the background of the notary's obligation to attach fingerprints to the receipt of the deed, how is the procedure for carrying out the obligation of the notary in attaching fingerprints to the deed of the deed, and the legal consequences of the deed and notary the fingers of the viewers on the minuta deed based on UUJN-P jo. UUJN. This research will be conducted using a type of normative juridical research with a type of legislative approach (concept approach) and a conceptual approach. The obligation of the notary to attach the fingerprint of the face in the background with the aim of anticipating if at any time the viewers deny their signature to the Minutes of Deed and this is an attitude of caution. In addition, regarding the procedure of implementation, regarding the obligation of the notary to attach fingerprints using the thumb/left thumb stamp and made on a new sheet or additional width. Normatively not attaching fingerprints does not give effect to the position of the certificate, the deed of the Notary is still valid and binding and has the power of proof that is perfect. For a Notary who does not carry out the obligation to attach a fingerprint to the Minute of Deed, the Notary may be subject to administrative sanctions.